ICT-ENABLED BOTTOM-UP ARCHITECTURAL DESIGN - Pak, Burak (ArchNet-IJAR, 2016)
This paper aims at discussing the potentials of bottom-up design practices in relation to the latest developments in Information and Communication Technologies (ICT) by making an in-depth review of inaugural cases. The first part of the study involves a literature study and the elaboration of basic strategies from the case study. The second part reframes the existing ICT tools and strategies and elaborates on their potentials to support the modes of participation performed in these cases. As a result, by distilling the created knowledge, the study reveals the potentials of novel modes of ICT-enabled design participation which exploit a set of collective action tools to support sustainable ways of self-organization and bottom-up design. The final part explains the relevance of these with solid examples and presents a hypothetical case for future implementation. The paper concludes with a brief reflection on the implications of the findings for the future of architectural design education.